Equity Returns, Firm-Specific Characteristics and Sector Rotation: Evidence from Turkey - GURIS, Selahattin; PALA, Aynur (International Journal of Economics and Financial Issues, 2014)
This paper examines the firm-spesific characteristics that affect on equity returns depending on sector rotation scheme throughout four financial cycle stages for an important emerging market, Turkey. For this purpose, using panel data for twenty-five non-financial equities selected from ISE-100 companies and twenty-six firm-specific characteristics in 2005Q1-2011Q1 it is analysed empirically whether firm-spesific factors that affect on equity returns differ among equity groups classified by sector rotation scheme throughout financial cycle stages. The firm-spesific characteristics have been reduced in five factor indexes which labelled liquidity, profitability, efficiency, growth, and valuation using factor analysis. We generated four dummy variables to classified equities using sector rotation scheme throughout financial cycle: “early expansion”, “late expansion”, “early recession”, and “late recession”. Panel regressions, with and without dummy variables, have been estimated using random coefficient model. In the full sample model, equity returns have been explained by only market return. In the with dummy variables model, equity returns of early and late recession equity groups explained by only market returns. Besides, in the early expansion and the late expansion groups, valuation factor is an important determinant of equity returns in addition to market return. Our finding shows that the factors that effect on equity returns differ among their belonging industries’ sensitivity to business cycle. Keywords: equity returns; business cycle; financial ratios; factor analysis; panel regression JEL Classifications: C33; G15; G120